Malay interrogative knowledge corpus - Sidi, Fatimah; A. Jabar, Marzanah; Selamat, Mohd Hasan; Abd Ghani, Abdul Azim; Sulaiman, Md. Nasir; Baharom, Salmi (Universiti Utara Malaysia, 2010)
The growth in the number of documents written in Malay language is enormously available on the web and intranets. There is a need to identify the information in the Malay documents that contain knowledge. This triggers the need to investigate the availability of knowledge in them. This study uses interrogative theory to identify knowledge from documents or texts. The results are expected to lead towards establishment of new set of interrogative rules for Malay corpus. This study contributes the interrogative knowledge identification thru the development of Malay Interrogative Knowledge Corpus (MalayIK-Corpus). It facilitates to explicitly capture and make available Malay knowledge representation in a knowledge-base system.